Statistical analysis of a new index of infection intensity - Silva, João Gilberto Corrêa da (Pesquisa Agropecuaria Brasileira, 2014)
The application of a new index of infection intensity, based on a suggestion by Amaral (1967), is considered by using the results of an experiment upon peach-tree rusts control.